Microwave and millimetre wave antipodal Vivaldi antenna with trapezoid‐shaped dielectric lens for imaging of construction materials. Issue 3 (1st February 2016) - Moosazadeh, Mahdi; Kharkovsky, Sergey; Case, Joseph T.
Abstract : High‐quality microwave and millimetre wave imaging of construction materials and structures requires ultra‐wideband (UWB) techniques to provide high‐range resolution as well as a reasonable penetration depth. A modified compact microwave and millimetre wave UWB antipodal Vivaldi antenna is designed and presented in this study. First, the conventional antipodal Vivaldi antenna is designed as a reference antenna. Then, to provide the desired frequency range (3.4–40 GHz) with increased gain at its lower frequencies, the slit edge technique is applied, thus creating a periodic slit edge antipodal Vivaldi antenna (PSEAVA). Finally, a trapezoid‐shaped dielectric lens (TDL) as an extension of the substrate is added and optimised to increase gain and directivity at higher frequencies of the frequency range, creating PSEAVA with a TDL (PSEAVA‐TDL). The results show that the PSEAVA‐TDL has the highest gain (up to 16 dB) and front‐to‐back ratio (up to 37.5 dB), and the narrowest half power beamwidth (down to 11.7°). A prototype of the proposed PSEAVA‐TDL with compact size of 40 × 90 × 0.508 mm 3 is fabricated and applied for the imaging of samples made of construction materials. High‐range resolution images of the samples are obtained with this antenna by using synthetic aperture radar algorithm.